2004
DOI: 10.1177/00222194040370040601
|View full text |Cite
|
Sign up to set email alerts
|

Specific Impairment in Developmental Reading Disabilities

Abstract: Children with developmental reading disabilities (RD) frequently display impaired working memory functioning. However, research has been divergent regarding the characteristics of the deficit. Our investigation addressed this controversy by assessing Baddeley's working memory model as a whole rather than focusing on particular aspects of it, as has been done by much of the research to date. Participants included 20 children with RD and 20 typical readers between the ages of 9 and 13. The phonological loop, vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
122
4
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(156 citation statements)
references
References 51 publications
19
122
4
11
Order By: Relevance
“…Data obtained in this research confi rms fi ndings of Kibby and Cohen (2008) and Kibby et al (2004), since there was a group difference in the verbal WM tasks (FW and BW digit spans); however, no differences were observed in the visuo-spatial WM tasks (Corsi blocks; De Jong et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Data obtained in this research confi rms fi ndings of Kibby and Cohen (2008) and Kibby et al (2004), since there was a group difference in the verbal WM tasks (FW and BW digit spans); however, no differences were observed in the visuo-spatial WM tasks (Corsi blocks; De Jong et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…According to Baddeley´s working memory model (WM; 2000), dyslexic children may present impairment in tasks involving the phonological loop ,even though most of these individuals have within average performances in skills that involve the visuo-spatial sketchpad, central executive and/or episodic buffer subcomponents (Kibby & Cohen, 2008;Kibby et al, 2004). Data obtained in this research confi rms fi ndings of Kibby and Cohen (2008) and Kibby et al (2004), since there was a group difference in the verbal WM tasks (FW and BW digit spans); however, no differences were observed in the visuo-spatial WM tasks (Corsi blocks; De Jong et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RD is primarily associated with linguistic problems, like impairments in phonological processing and slower serial naming speed (Pennington, Groisser, & Welsh, 1993;Purvis & Tannock, 2000;Rucklidge & Tannock, 2002;Semrud-Clikeman, Guy, Griffin, & Hynd, 2000;Willcutt et al, 2001), EF deficits, like inhibition and WM problems have also been reported (e.g., Purvis & Tannock, 2000;Swanson, Mink, Bocian, 1999;van der Schoot, Licht, Horsley, & Sergeant, 2000;Van De Voorde, Roeyers, Verté, & Wiersema, 2010). In terms of Baddeley's WM model, results have been in favour of no problems, only verbal, or both verbal and visual-spatial WM problems (e.g., Kibby, Marks, Morgan, & Long, 2004;Savage, Lavers, & Pillay, 2007;Swanson, Ashbaker, & Lee, 1996).…”
mentioning
confidence: 99%
“…Neurological disharmony may impact the central executive (Kibby et al, 2004) and working memory (Willis, 2008), and is believed to contribute to challenges with attention, organization, and recall. The relationship of cognitive challenges to learning informed the explicit instruction model of Archer and Hughes (2011), which requires identifying and presenting critical information, and deliberately explaining and demonstrating procedures and concepts.…”
Section: Reduced Cognitive Loadsmentioning
confidence: 99%